On the second largest distance eigenvalue of a graph. Issue 5 (4th May 2017) - Liu, Ruifang; Xue, Jie; Guo, Litao
Abstract : Let G be a simple connected graph of order n and D ( G ) be the distance matrix of G . Suppose that is the distance spectrum of G . A graph G is said to be determined by its D -spectrum if any graph with the same distance spectrum as G is isomorphic to G . In this paper, we consider spectral characterization on the second largest distance eigenvalue of graphs, and prove that the graphs with are determined by their D -spectra.